Screening and Verification of Key Ubiquitination Genes Related to Immune Infiltration in Stage III/IV Hepatocellular Carcinoma - Tang Y; Cao J; Peng R; Mao X; Su B; Tang H; Tu D; Zhou J; Jiang G; Jin S; Wang Q; Zhang C; et al. (Journal of Hepatocellular Carcinoma, 2023)
Yuhong Tang,1,* Jun Cao,1,* Rui Peng,1 Xingkang Mao,1 Bingbing Su,1 Hao Tang,1 Daoyuan Tu,1 Jie Zhou,1 Guoqing Jiang,1 Shengjie Jin,1 Qian Wang,1 Chen Zhang,2 Renjie Liu,1 Chi Zhang,1,3 Dousheng Bai1,3 1Department of Hepatobiliary Surgery, Clinical Medical College, Yangzhou University, Yangzhou, People’s Republic of China; 2The Second Affiliated Hospital of Xuzhou Medical University, Xuzhou, People’s Republic of China; 3General Surgery Institute of Yangzhou, Yangzhou University, Yangzhou, People’s Republic of China*These authors contributed equally to this workCorrespondence: Dousheng Bai; Chi Zhang, Department of Hepatobiliary Surgery, Clinical Medical College, Yangzhou University, 98 West Nantong Road, Yangzhou, 225000, People’s Republic of China, Email drbaidousheng@yzu.edu.cn; zc17212850@163.comIntroduction: Immune checkpoint therapy (ICIs) effectively improves the prognosis of advanced (stage III/IV) hepatocellular carcinoma (HCC) patients. However, its objective response rate (ORR) is below 20%, significantly limiting ICI use in advanced HCC patients. The level of tumour immune infiltration influences ICI response rate. Recent studies have found ubiquitinase to be an important factor that regulates tumour immune infiltration. Therefore, the aim of this study is to explore the key ubiquitination genes that regulate immune infiltration in advanced HCC and further validate them.Methods: A biotechnological process was performed as a means of classifying 90 advanced HCC patients into three immune subtypes and identifying associations with immune infiltration in the co-expressed modules. Ubiquitination-related genes were then screened with WGCNA. Gene enrichment analysis was performed for the target module and 30 hub genes were screened out by protein–protein interaction network (PPI). ssGSEA, single-gene sequencing and the MCP counter were used for exploring immune infiltration. TIDE score was applied for predicting drug efficacy and GSEA was used for exploring potential pathways. Finally, GRB2 expression in HCC tissue was validated by in vitro experiments.Results: GRB2 expression was found to have a significant correlation with the pathological stage and prognosis of HCC patients and a positive correlation with immune infiltration and tumour mutation burden (TMB). In addition, significant correlations with the efficacy of ICIs, sorafenib and transarterial chemoembolization (TACE) were identified. GRB2 was found to be most significantly associated with the JAK-STAT signalling pathway and cytosolic DNA sensing pathway. Finally, it was found that GRB2 expression is closely related to the prognosis, tumour size and TMN stage.Conclusion: A significant association was observed between the ubiquitinated gene GRB2 and the prognosis and immune infiltration of advanced HCC patients and it may potentially be used for predicting therapy efficacy in advanced HCC patients in the future.Keywords: ubiquitination, growth factor receptor-binding protein 2, liver cancer, tumour-infiltrating immune cells